2010
DOI: 10.1371/journal.pone.0009824
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Reproductive Allocation, Growth, Defense and Herbivory in Three Dioecious Neotropical Palms

Abstract: BackgroundFrequently, in dioecious plants, female plants allocate more resources to reproduction than male plants. Therefore it is expected that asymmetrical allocation to reproduction may lead to a reproduction-growth tradeoff, whereby female plants grow less than male plants, but invest more in defenses and thus experience lower herbivory than male plants.Methodology/Principal FindingsWe tested these expectations by comparing resource allocation to reproduction, growth and defense and its consequences on her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 54 publications
4
55
2
1
Order By: Relevance
“…Our findings partially support previous thinking about dioecy effects on plant traits and arthropod communities. Theory predicts that, due to tradeoffs between growth, reproduction, and defense, female plants invest more energy in reproduction and in defensive traits (lower herbivory) and in turn tend to exhibit decreased growth relative to male plants (Cox 1982;Cornelissen and Stiling 2005;Cepeda-Cornejo and Dirzo 2010). Supporting this hypothesis, we found that female B. salicifolia plants produced more flowers than male plants.…”
Section: Discussionsupporting
confidence: 77%
“…Our findings partially support previous thinking about dioecy effects on plant traits and arthropod communities. Theory predicts that, due to tradeoffs between growth, reproduction, and defense, female plants invest more energy in reproduction and in defensive traits (lower herbivory) and in turn tend to exhibit decreased growth relative to male plants (Cox 1982;Cornelissen and Stiling 2005;Cepeda-Cornejo and Dirzo 2010). Supporting this hypothesis, we found that female B. salicifolia plants produced more flowers than male plants.…”
Section: Discussionsupporting
confidence: 77%
“…As proposed by theory on dioecious species (Delph 1999;Geber, Dawson & Delph 1999;Obeso 2002;Cepeda-Cornejo & Dirzo 2010), Poa genders were dimorphic in traits related to resource allocation. As predicted (Prediction 1), females had lower vegetative growth rates (Table 1) but they were better defended against herbivores than males.…”
Section: Discussionmentioning
confidence: 87%
“…We also hypothesize that those differences in traits determine, indirectly, their interaction with domestic herbivores. The predictions were the following: 1 Females will have lower vegetative growth than males (Lloyd & Webb 1977;Obeso 2002), will also be better defended than males, and hence less preferred by natural herbivores (Coley, Bryant & Chapin 1985;Jing & Coley 1990;Herms & Mattson 1992;Cepeda-Cornejo & Dirzo 2010). 2 Female biomass will be more negatively affected by the competition with other grass species than males because of slower female growth and higher reproductive requirements (Lloyd & Webb 1977).…”
mentioning
confidence: 99%
“…Mauritiinae, Ceroxyleae). Dioecy implies different strategies of resource allocation depending on the sex of the plant, and consequently differential selective effects on male and female plants (Cepeda-Cornejo & Dirzo, 2010). Arecoideae is the most diverse palm subfamily in tropical America with 39 genera, mostly monoecious, with the exception of the dioecious Chamaedorea and Wendlandiella.…”
Section: Reproductive Traitsmentioning
confidence: 99%